Visual Exploration Area in Neglect: A New Analysis Method for Video-Oculography Data Based on Foveal Vision - Kaufmann, Brigitte Charlotte; Knobel, Samuel Elia Johannes; Nef, Tobias; Müri, René Martin; Cazzoli, Dario; Nyffeler, Thomas (Frontiers in Neuroscience, 2020)
Video-oculography during Free Visual Exploration (FVE) is a valuable tool to evaluate visual attention spatial allocation in neglect patients after right-hemispheric stroke. In conventional FVE analyses, the position of a visual fixation is conceived as a single point in space. Here, we describe a new, complementary method to analyse FVE data, based on foveal vision, leading to an accurate estimate of the portion of the picture that was effectively explored. In 15 neglect patients and 20 healthy controls, visual exploration areas (i.e., considering 1°visual angle around every single fixation) were computed. Furthermore, the proportion of single and overlapping fixations was analysed. Overlapping fixations were further categorized into capture fixations (successive overlapping fixation, putatively reflecting problem of disengagement) and re-capture fixations (temporally distant overlapping fixations, putatively reflecting spatial working memory deficits). The results of this new analysis approach were compared to the ones of conventional approaches. Conventional analyses showed the typical visual attention deficits in neglect patients versus healthy controls: significantly less fixations and time spent within the left, and significantly more fixations and time spent within the right screen half. According the results of our new approach, patients showed a significantly smaller visual exploration area within the left screen half. However, the right visual exploration area did not differ between groups. Furthermore, in neglect patients, the proportion of overlapping fixations within the right screen half was significantly higher than within the left screen half, as well as significantly higher than in healthy controls within either screen halves. Whereas neglect patients showed significantly more capture fixations than healthy controls, the number of re-capture fixations did not differ between groups. These results suggest that, in neglect patients, the efficiency of visual exploration is also reduced within the right screen half and that impaired disengagement might be an important mechanism leading to overlapping fixations. Our new analysis of the visual exploration area, based on foveal vision, may be a promising, additional approach in visual attention research. It allows to accurately measure the portion of the picture that was effectively explored, disentangle single from overlapping fixations, and distinguish between capture and re-capture fixations.